ANALISIS PERUBAHAN MODIFIKASI NOKEN KULIT KAYU DENGAN TOTAL QUALITY MANAGEMENT - Morip, Yes; Tajuddin, Tamrin; Amri, Irman; Histiarini, Aprisa Rian; Maulana, Mirga Maulana (Industrial Engineering Journal – System, 2023)
In the Papua Noken bag production process, the problem that often occurs is a lack ofcreativity in modifying the product, caused by lack of trained workers, poor sorting ofraw materials, improper function of tools, not using dyes and no place to store finishedproducts. This research aims to analyze quality control on changes to modifications ofPapuan noken. The steps are to collect data using check sheets, Fishbone Diagrams,Implementation of improvements and Sales Analysis. The results of the analysis showthat with the Quality Control approach, it is known that the factors that influencechanges in the Wamena Noken modification include material, human,machine/equipment, and method factors. The change that stands out the most is theincrease in production capacity from only one kind and following conditions to four oreven more types.